2021
DOI: 10.3390/jfmk6010007
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Body Composition, Maximum Strength, Power Characteristics with Sprinting, Jumping, and Intermittent Endurance Performance in Male Intercollegiate Soccer Players

Abstract: The purpose of this study was to determine the relationships between body composition, strength, power characteristics, sprinting, jumping, and intermittent endurance performance in collegiate male players. Twenty-three players participated (19.7 ± 1.6 yrs; 71.8 ± 7.1 kg; 176.5 ± 5.1 cm). Measurements of interest in body composition included body fat percentage (BF%), lean body mass (LBM), and body mass (BM). Power characteristics were measured with an unloaded squat jump (SJ0) and loaded SJ at 20 kg (SJ20) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…However, the correlation coefficient of the maximum vertical component of GRF was more significant than the RFD. The results of this study are consistent with other studies that have shown a strong correlation between power and vertical jump performance (27,28). In the study of Ishida et al, the correlation coefficient between power and countermovement vertical jump height was obtained as 0.91 (27).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the correlation coefficient of the maximum vertical component of GRF was more significant than the RFD. The results of this study are consistent with other studies that have shown a strong correlation between power and vertical jump performance (27,28). In the study of Ishida et al, the correlation coefficient between power and countermovement vertical jump height was obtained as 0.91 (27).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the correlation coefficient between body fat percentage and jump height was found to be -0.491, which is in agreement with the coefficient of -0.39 in the research of Legg et al and the coefficient of -0.35 indicated by Pérez-López et al (18,19). On the contrary, the study by Ishida et al showed no significant relationship between vertical jump height and body fat percentage in male soccer players on a university team (27). One of the reasons for the higher correlation coefficient between body fat percentage and jump height in this study than in other studies is that the subjects of this study were professional athletes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are in line with our previous study [ 42 ] in which high performers in a vertical jump test presented a higher BMI (23.9 ± 1.25 vs. 22.8 ± 1.10 kg/m 2 ; p = 0.03, ES = −0.91) and corrected arm muscle area (59.39 ± 6.64 vs. 50.74 ± 6.82 cm 2 ), which is already considered a predictor of sprint performance in young soccer players [ 28 ]. This is not surprising as CMJ has also been found to be directly correlated with 10 m and 20 m sprint performances [ 43 , 44 ] and relative strength during dynamic 1 RM squat and power [ 45 ]. Accordingly, Suarez-Arrones et al [ 18 ] found similar results in a study with elite professional soccer players of the Italian Serie A.…”
Section: Discussionmentioning
confidence: 95%
“…The monitoring data can inform the practitioners about a current physical and psychological state of the player and assist their decision-making for TL management. Common measures of an athlete monitoring program, particularly for fatigue management, include the Global Navigation Satellite System (GNSS), subjective recovery and stress state, and the countermovement jump (CMJ) (Sams et al, 2018;Travis et al, 2018Travis et al, , 2020Walker et al, 2019;McFadden et al, 2020;Draper et al, 2021;Ishida et al, 2021c). The GNSS devices have been used to quantify external TL, including the TL of soccer match play, which have been associated with acute muscle damage and the alterations in neuromuscular performance (de Hoyo et al, 2016;Russell et al, 2016;Coppalle et al, 2019;Wiig et al, 2019;Ishida et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%